Antonin Artaud's writing bodies - Morfee, Adrian (Oxford modern languages and literature monographs., 2005)
This book studies the development of Artaud's thinking throughout his career on such issues as the body, theology, language, and identity. His late poetry is discussed in depth and new attention is paid to the verbal details of his writing and to the way he builds up his ideas. Artaud emerges as a man of ideas performing disturbing conceptual work, but needs to be considered not as a contestatory psychotic but as a writer of the first order. - ;Antonin Artaud (1896-1948), perhaps best known as a dramatic theorist, is an important but extremely difficult writer. This book studies the developmen.